Antiviral and virucidal activities against herpes simplex viruses of umesu phenolics extracted from Japanese apricot. (22nd August 2019) - Nishide, Mitsunori; Ikeda, Keiko; Mimura, Hisa; Yoshida, Minoru; Mitani, Takahiko; Hajime Koyama, Augustine
Abstract: Umesu phenolics were obtained from the salt extracts of Japanese apricot (Nanko‐mume cultivar of Prunus mume Sieb. et Zucc.) as purified phenolics. The antiviral activities of umesu phenolics obtained were then examined against herpes simplex virus type 1 (HSV‐1) and type 2 (HSV‐2), enveloped DNA viruses. The phenolics inhibited the multiplication of these viruses when added to the culture media of the infected cells. This inhibition occurred at phenolic concentrations at which they showed no severe cytotoxicity. One‐step growth experiments showed that the eclipse period in the HSV‐1 multiplication process was extended in the presence of umesu phenolics and that the addition of phenolics after the completion of viral DNA replication did not affect their multiplication. More drastic effects were observed on virucidal activities against HSV‐1 and HSV‐2; the infectivity decreased to 0.0001 when infected cells were incubated with 3 mg/ml phenolics at 30°C for 5 min. These results demonstrate the antiviral and virucidal activities of umesu phenolics and suggest a potential pharmacological use for these phenolics as a sanitizing or preventive medicine against superficial HSV infections.